Research trends and hotspots in the relationship between outdoor activities and myopia: A bibliometric analysis based on the web of science database from 2006 to 2021 - Mu, Jingfeng; Zhong, Haoxi; Zeng, Dan; Fan, Jingjie; Jiang, Mingjie; Liu, Meizhou; Shuai, Xinyi; Chen, Yanjie; Zhang, Shaochong (Frontiers in Public Health, 2022)
Objectives: This study aimed to explore the current status, hotspots, and emerging research trends regarding the relationship between outdoor activities and myopia. Methods: Publications on the relationship between outdoor activities and myopia from 2006 to 2021 were collected from the Web of Science Core Collection database. CiteSpace (version 6.1.R2) was used to performed a bibliometric analysis, and R software (version 4.1.0) was used to visualize the trends and hot map of publications. Results: A total of 640 publications were collected and analyzed in the present study. China was the major contributor (n=204), followed by the United States of America (n=181) and Australia (n=137). The United States of America had the most extensive foreign cooperation (centrality=0.25), followed by Australia (centrality=0.20). The National University of Singapore contributed the largest number of publications (n=48), followed by Sun Yat-Sen University (n=41) and the Australian National University (n=41). Among institutions, Cardiff University in the United Kingdom had the most extensive foreign cooperation (centrality=0.12), followed by the National University of Singapore (centrality=0.11). Saw S from Singapore had the largest number of publications (n=39), followed by Morgan I from Australia (n=27) and Jonas J from Germany (n=23). Investigative ophthalmology & visual science is the most important journal to study the relationship between outdoor activities and myopia. “Global Prevalence of Myopia and High Myopia and Temporal Trends from 2000 through 2050” published by Holden BA was the most cited paper in this field with 177 citations. Co-occurrence and burst analyses of keywords showed that research trends and hotspots in this field focused mainly on “risk,” “prevention” and “school”. Conclusions: The influence of outdoor activities on myopia remains a concern. In the future, deeper cooperation between countries or institutions is required to explore the effects of outdoor activities on myopia. Outdoor activities for the prevention of myopia and reduction of the risk of myopia among school students may be the focus of future research.